Gender differences in irritable bowel syndrome: The interpersonal connection - Thakur, Elyse R. (Neurogastroenterol Motil, 2015)
BACKGROUND: While IBS affects women more often than men, the reasons are unclear. Research on the female preponderance of IBS has focused on gender differences in sex-linked biological processes; much less attention has been paid to the role of psychosocial factors. Interpersonal difficulties may be one source of stress that may significantly impact women with IBS. Because of the importance that women attach to relationships, we suspected they would be more reactive to interpersonal stress. METHODS: 283 (M age = 41 yrs., F = 80%), Rome III-diagnosed IBS patients completed a test battery that included the IBS Symptom Severity Scale, McGill Pain Questionnaire, Inventory of Interpersonal Problems (IIP), Interpersonal Support Evaluation List (social support), Negative Interactions Scale, Brief Symptom Inventory (distress), Beck Depression Inventory, Anxiety Sensitivity Inventory, and IBS-Quality of Life as part of baseline assessment of an NIH trial. KEY RESULTS: Males scored higher on 2 IIP scales reflecting a hostile-dominant interpersonal pattern, and reported less social support. The quality of relationship problems (more interpersonal difficulties, lower support) correlated with IBS symptom severity as measured mainly by gastroenterologists. CONCLUSIONS & INFERENCES: Male, not female, IBS patients reported more interpersonal difficulties. Male patients -- a population for whom little is known -- are characterized by hostile-dominant interpersonal problems. This finding has clinical importance, given that relationship problems may influence MDs’ estimation of IBS symptom severity and undermine the physician-patient relationship.